Pendidikan Islam di Era Digital: Peluang dan Tantangan Transformasi Teknologi di Pondok Tahfiizh Al Qur'an Al-Bashiirah Kota Baru - Dyah Wulandari; Wishal Luthfikha; Vina Nuranisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The use of technology in education is one of the main pillars of transformational education, because technology has great potential to facilitate this transformation. The importance of technology used by Islamic boarding schools is the main thing needed by students to carry out educational transformation. By adopting a transformational education approach that is strengthened by technology, Islamic boarding schools can prepare their students to become future leaders who are adaptive, innovative, and competitive in an increasingly connected and technology-driven world. The purpose of this study is to analyze the opportunities and challenges of technological transformationat the Al-Bashiirah Al-Qur'an Memorization Boarding School.This research was conducted at the Al-Bashiirah Al Qur'an Tahfiizh Boarding School in New City. The techniques used in data collection were structured interviews, non-participant observation and documentation. The results of the study showed that: 1) The technology design used Google spreadsheets, data input was carried out together by involving the finance department, homeroom teachers and tahfidz teachers and the selection of technology applications considered aspects of affordable costs for their use, 2) The digital development dimension, namely by using the information system for the achievement of students' hifdzul Qur'an and students' financial balance data, 3) Digital competence at the Al-Qur'an Al-Bashiirah Tahfidz Boarding School hasfulfill basic skills in the use of information and communication technology, and 4) The benefits of digital transformation at the Al-Bashiirah Al-Qur'an Tahfidz Boarding School have a significant impact on the development of the institution.